Influence of Cu-Doping on Linear and Nonlinear Optical Properties of High-Quality ZnO Thin Films Obtained by Spin-Coating Technique - Abdelkader Mohammedi (Université de M'sila, 2022)
To study the effect of Cu concentration on morphological, structural, linear and nonlinear optical properties, copper-doped ZnO thin films are grown by sol–gel/ spin-coating technique on the glass substrates. Scanning electron microscopy (SEM) images reveal that the surface morphology is homogeneous with good adhesion to the glass substrate. The energy dispersive X-ray spectroscopy (EDS) spectra confirm that Zn, O, and Cu elements are present in ZnO films. The X-ray diffraction (XRD) pattern of Cu-doped ZnO is dominated by (002) peak, indicating an upstanding ZnO nanorods array growing along the c-axis. The optical bandgap of Cu-doped ZnO thin films, calculated from optical transmission spectra, is found to decrease with the increase in copper concentration. The refractive index dispersion curve of ZnO films is subjected to the single-oscillator model. The optical dispersion parameters Eo, Ed, and n∞, the nonlinear refractive index, and nonlinear optical susceptibility are calculated and interpreted